Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3109/0886022x.2013.800459
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the syndrome of rapid onset end-stage renal disease (SORO-ESRD) in the acute kidney injury (AKI) literature – preventable causes of AKI and SORO-ESRD – a call for re-engineering of nephrology practice paradigms

Abstract: The contribution of SORO-ESRD to the global ESRD pandemic, the impact of SORO-ESRD on AV-Fistula planning, any differential behavior of SORO-ESRD versus classic ESRD in terms of mortality outcomes and any predisposing factors to SORO-ESRD as advanced age and nephrotoxic exposure all call for serious research study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
(65 reference statements)
0
11
0
1
Order By: Relevance
“…Among the various risk factors, CCI score ≥4 points has the highest predictive value. In addition to correcting the renal artery stenosis, the optimal treatment of hypertension, diabetes mellitus, cerebrovascular diseases and other accompanying diseases can really improve the prognosis of patients; before the therapeutic regimen is developed for ARAS patients, the comorbidity of patients must be taken into full account, and the individualized therapeutic regimen should be developed (2426). …”
Section: Discussionmentioning
confidence: 99%
“…Among the various risk factors, CCI score ≥4 points has the highest predictive value. In addition to correcting the renal artery stenosis, the optimal treatment of hypertension, diabetes mellitus, cerebrovascular diseases and other accompanying diseases can really improve the prognosis of patients; before the therapeutic regimen is developed for ARAS patients, the comorbidity of patients must be taken into full account, and the individualized therapeutic regimen should be developed (2426). …”
Section: Discussionmentioning
confidence: 99%
“…Our recent review of the AKI literature, 1975-2010, had unearthed 16 individual AKI reports that described patients with features consistent with our working diagnosis of SORO-ESRD. [215] Emphatically, an accompanying editorial to one of these 16 studies, published in the Quarterly Journal Of Medicine in 1996, had referred to similar observations of ESRD rapidly following AKI in patients seen at The General Infirmary at Leeds, United Kingdom as “acute irreversible renal failure”. [16] We have concluded that this indeed was a very apt description of the syndrome after which we had coined the new name, the syndrome of rapid onset end stage renal disease, or SORO-ESRD, in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…[16] We have concluded that this indeed was a very apt description of the syndrome after which we had coined the new name, the syndrome of rapid onset end stage renal disease, or SORO-ESRD, in 2010. [2111215]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations